A Digital Painting Learning Model Using Mixed-Reality Technology to Develop Practical Skills in Character Design for Animation - Vipusit Piankarnka; Kridsanapong Lertbumroongchai; Pallop Piriyasurawong (Advances in Human-Computer Interaction)
This research aims to (1) synthesize the digital painting learning process by using mixed-reality technology to develop practical skills in character design for animation and (2) develop and evaluate digital painting learning models using mixed-reality technology to develop practical skills in character design for animation. This research was conducted by studying documentation and related research and designing digital painting learning models using mixed-reality technology to develop practical skills in character design for animation. Using a questionnaire, a total of 9 experts evaluated the model’s suitability. The statistics used in the research were the mean and standard deviation. The study found that a component of the digital painting learning process involves using mixed-reality technology to develop practical skills in character design for animation. It consists of the following four components: (1) input data, (2) the digital painting learning process, (3) output assessment, and (4) feedback. The expert’s evaluation of the model’s suitability found that the digital painting learning model using mixed-reality technology to develop practical skills in character design for animation was at the highest level (mean ± SD = 4.38 ± 0.21). This research is beneficial to faculty who teach character design and development for animation. The results of the study can be applied to teaching and learning.